Analisis Efektivitas Pelaksanaan Program PPL II Melalui Model CIPP di Madura - Mukhid, Abd; Habibullah, Mosleh (LP2M IAI Miftahul Ulum Pamekasan, 2022)
The research aims to determine the effectiveness of implementing PPL 2 in Madura through analysis of respondents regarding the implementation of PPL 2 or PM 2 in terms of context variables, input variables, process variables and product/result variables. This research uses a quantitative approach with a type of evaluation. The data source used was PPL 2 students of the STAIN Pamekasan Tarbiyah Department. Data were collected using questionnaire techniques and analyzed using descriptive statistics. The results of the research show that the implementation of PPL 2 in Madura is classified as being in the category of sufficient effectiveness based on the recapitulation of the T Score calculation for each variable as in Table 2 above. The calculation results show that the context variable is positive, the input variable is positive, and the process variable is positive. the result is negative, and the product variable is positive (CIPP = + + - +).